Design of a dual-band MIMO dielectric resonator antenna with pattern diversity for WiMAX and WLAN applications - Khan, Ahmad Ali (Electromagnetics Academy, 2016)
In this paper, a dual-band multiple-input multiple-output dielectric resonator antenna (DRA) with pattern diversity is presented. L-shape of the DRA produces patterns diversity at the lower band whereas, at the upper band, it is caused by exciting TEx 121/TEy 211 mode in the DRA. Two copper strips are pasted at the corner of the dielectric radiator to improve matching at both the bands. A cylindrical air-gap introduced in the radiator improves isolation up to 25 dB and 20 dB at lower and upper frequency bands, respectively. The MIMO system possesses pattern diversity and isolation without applying any special decoupling technique. The design covers the WiMAX and WLAN bands at 3.6 and 5.2GHz, respectively. Simulated and measured reflection coefficients, envelope correlation, diversity gain and mean effective gain, are in good agreement.